Related Party Transactions and Corporate Governance in Business Group: Evidence from Indonesia - Perdana Wahyu Santosa; Sovi Ismawati Rahayu; Zainal Zawir Simon; Martua Eliakim Tambunan (Universitas Hayam Wuruk Perbanas, 2022)
This paper aims to offer new evidence as to how sub-related party transactions (RPTs) can be related to corporate governance for Indonesia's business group. We address an ongoing theoretical tension and some recent research in the RPTs literature by focusing on revenue, expenses, loans, and receivables. Business groups are classified by size or market capitalization. This paper examines whether RPTs in the business group relate with domestic/foreign shareholders, independent board/commissioner, and firm size as controlling factors. The business groups wereselected through purposive sampling that met the analysis criteria with their typology in the population of business groups listed on IDX. We used panel data analysis for four models. This relationship is more pronounced than some recent research for business group firms and firms with more highly concentrated foreign ownership regarding the effect RPTs on revenue, expenses, loans, and receivables. Related to the controlling variable, firm size shows a significant effect on every sub RPTs. The results may imply that foreign ownership exploits Indonesia with expenses such as cross-border transactions of capital goods, intangible property (royalty), intra-firm services, and the cost of debt. Therefore, there is a need for a balanced interest for government and business in Indonesia via foreign directinvestment with corporate governance implementation and adaptive regulation.